Direct asymmetric allylic alkenylation of N-itaconimides with Morita–Baylis–Hillman carbonates - Yang, Wenguo (2013)
The asymmetric allylic alkenylation of Morita–Baylis–Hillman (MBH) carbonates with N-itaconimides as nucleophiles has been developed using a commercially available Cinchona alkaloid catalyst. A variety of multifunctional chiral α-methylene-β-maleimide esters were attained in moderate to excellent yields (up to 99%) and good to excellent enantioselectivities (up to 91% ee). The origin of the regio- and stereoselectivity was verified by DFT methods. Calculated geometries and relative energies of various transition states strongly support the observed regio- and enantioselectivity.